Keberadaan Hukum Pidana Adat dalam Ruang Lingkup Hukum Pidana Indonesia - Iman Hidayat (Wajah Hukum, 2022)
The existence of customary criminal law in a society reflects the life of the community, and each region has its own unwritten criminal law which is coded according to local customs. In this study the author uses empirical juridical research methods. The type of research in this study is empirical juridical which is carried out directly by looking at customary law in Indonesia with the research specification being descriptive. Sources of data are field research and literature. This study uses a legal approach with data collection techniques using interviews and qualitative data analysis. The results of this study are that the existence of customary criminal law within the scope of Indonesian criminal law is very necessary because not every act if positive criminal law is used will take a long time, while customary criminal law is faster to resolve because it uses the local customary law system so that it should Customary criminal law must be used as Indonesian criminal law.